2015
DOI: 10.1002/admi.201500330
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobicity vs. Ice Adhesion: The Quandary of Robust Icephobic Surface Design

Abstract: to spectacular rebound events of droplets upon impact [ 1,2 ] and ultra-low adhesion to water. [3][4][5][6][7][8][9] Unfortunately, depending on surface texture, superhydrophobic (nonwetting) properties can be lost either by water condensation in the texture [ 10 ] or drop impact beyond a texture-specifi c velocity (critical velocity), when rebound to sticky transition occurs. [ 11 ] In both cases, the micro-/nanocavities of the surface texture are fi lled with water transitioning the droplet from a non-wetted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…The nf surface also showed a high impalement resistance, resisting jets with speeds of 11 m/s (~ 840), which is consistent with the previous study on the similar nanofiber structures [23]. Note that, the previous study [23] showed that similar nanofiber structures on a smooth aluminum surface can repel impact of 2-mm sized water drops up to ~3000. However, the surfaces were not tested with jet impact, which offers a more severe test of durability.…”
Section: Discussionsupporting
confidence: 89%
“…The nf surface also showed a high impalement resistance, resisting jets with speeds of 11 m/s (~ 840), which is consistent with the previous study on the similar nanofiber structures [23]. Note that, the previous study [23] showed that similar nanofiber structures on a smooth aluminum surface can repel impact of 2-mm sized water drops up to ~3000. However, the surfaces were not tested with jet impact, which offers a more severe test of durability.…”
Section: Discussionsupporting
confidence: 89%
“…Anti-icing coatings are highly valued for preventing or alleviating adverse consequences of ice accretion on airplanes, marine structures, satellites, weapon systems, and energy-harvesting devices. In the past two decades, tremendous efforts have been devoted to the study of anti-icing performance of superhydrophobic coatings inspired by the lotus effect [1] and coatings are mechanically weak. An earlier study of transparent anti-icing coating was conducted by Kimura et al, [8] and one of their reported coatings was water-repellent and transparent.…”
Section: Introductionmentioning
confidence: 99%
“…A more likely cause for the behaviour in Figure 14 is the current experimental setup which means that the load/force is not applied at the surface, but at a distance from the surface. As detailed by Maitra et al [38], this results in the simultaneous action of tensile and shear stresses, which can yield different results to those obtained when applying shear forces alone.…”
Section: Effect Of Fixture Surface Temperaturementioning
confidence: 98%
“…The fixture was carefully located to let the freelyhanging chain rest directly above the M6 hole in the specimens where the force would be applied. To apply ideal shear, the point of application of the force should be as close as possible to the workpiece/ice plate contact line [38], to avoid the introduction of tensile forces. Due to the nature of the experimental setup where the connection between the Instron and the workpiece was made using the chain, and the fact that the workpiece specimens were place at the centre of surface of much greater area, applying the shear force immediately at the ice plate surface was not possible.…”
Section: Shear Loading Setupmentioning
confidence: 99%